Analisis Implementasi Akuntansi Sektor Publik Dalam Meningkatkan Transparansi dan Akuntabilitas Keuangan Pemerintah Daerah Lampung - Nurohmayni Putri (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This study aims to analyze the implementation of public sector accounting in increasing financial transparency and accountability in local governments. The research method used is qualitative descriptive with data collection techniques through interviews, observations, and documentation. The results show that the effective implementation of public sector accounting can increase financial transparency and accountability, although there are still several obstacles such as the lack of competent human resources and adequate technological infrastructure.